IMPLEMENTATION OF GOOD GOVERNANCE IN PUBLIC SERVICES IN RAWAMERTA DISTRICT, KARAWANG REGENCY - Zainul Djumadin (Sean Institute, 2023)
Applying the principles of good governance to reflect the absolute needs of the majority of society in order to create a political system that is more supportive of the importance of governance by the people in accordance with universal democratic principles. This can also be a driving force for the formation of the desired political system that involves various good governance processes starting from the formulation of public policy, development management, to the implementation of a transparent, efficient and effective public bureaucracy to improve people's welfare. This research aims to analyze and evaluate the application of Good Governance principles in the context of public services in Rawamerta District, Karawang Regency. The method used in this research is descriptive qualitative. The research results show that the implementation of Good Governance principles in public services in Rawamerta District is still experiencing obstacles. Limited service facilities due to limited funds, low levels of understanding by officials regarding Good Governance, and public awareness that needs to be increased are the main obstacles. There is an urgent need to improve service facilities, intensive training for officers, and increase public awareness. The principle of participation is the key to paradigm change, where involving the community from the start in formulating service needs can increase the responsiveness and relevance of public services. With the commitment of sub-district leaders, collaboration between agencies and active community participation, it is hoped that the quality of public services can be improved, making them more efficient, effective and in line with the demands of the times.